Antioxidant and functional properties of cowhide collagen peptides. Issue 5 (6th April 2021) - Xie, Zhike; Wang, Xuguang; Yu, Shuyan; He, Ming; Yu, Shaoxuan; Xiao, Haifang; Song, Yuanda
Abstract : Abstract: In the present study, antioxidant activities and functional properties of cowhide collagen antioxidant peptides (CCAPs) with different molecular weight (MW) were investigated. The optimum preparation conditions of CCAPs were hydrolysis time of 1.53 hr, temperature of 54.9 °C, pH 7.38, and neutral enzyme to trypsin ratio of 0.048 g: 0.016 g according to single factor test and response surface methodology (RSM). Three fractions (CCAP‐I, CCAP‐II, and CCAP‐III) were obtained by ultrafiltration and lyophilization. Antioxidant activities revealed that CCAP‐III had high reducing power activity (0.323 ± 0.035) and scavenging effect on 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radicals (64.30 ± 5.99%), 2, 2‐azino‐bis‐(3‐ethylbenzothiazoline)‐6‐sulfonic acid (ABTS) radicals (75.25 ± 3.14%), and hydroxyl radicals (68.26 ± 6.74%) compared to the other fractions. In addition, LC‐MS/MS analysis showed that Ala‐Gly‐Glu‐Arg, Gly‐Ile‐Ala‐Gly‐Glu‐Arg, Gly‐Pro‐Ala‐Gly‐Pro‐Ala‐Gly‐Pro‐Arg, Gly‐Val‐Val‐Gly‐Pro‐Glu‐Gly‐Ala‐Arg and Gly‐Phe‐Ser‐Gly‐Leu‐Asp‐Gly‐Ala‐Lys were the major peptides of CCAP‐III. CCAP‐III showed good hygroscopicity (HYG), water holding capacity (WHC), and oil holding capacity (OHC) when compared with CCAP‐I and CCAP‐II. However, CCAP‐II has great emulsifying properties, and CCAP‐I has excellent foaming properties. Therefore, CCAPs can be used as a promising source of functional peptides with antioxidant properties. Practical Application: This study demonstrated the peptides of cowhide collagen has superior antioxidant and functional properties. This study provided a scientific basis for the preparation of antioxidant peptides from cowhide collagen.